Laser diode area melting for high speed additive manufacturing of metallic components. (5th March 2017) - Zavala-Arredondo, Miguel; Boone, Nicholas; Willmott, Jon; Childs, David T.D.; Ivanov, Pavlo; Groom, Kristian M.; Mumtaz, Kamran
Abstract: Additive manufacturing processes have been developed to a stage where they can now be routinely used to manufacture net-shape high-value components. Selective Laser Melting (SLM) comprises of either a single or multiple deflected high energy fibre laser source(s) to raster scan, melt and fuse layers of metallic powdered feedstock. However this deflected laser raster scanning methodology is high cost, energy inefficient and encounters significant limitations on output productivity due to the rate of feedstock melting. This work details the development of a new additive manufacturing process known as Diode Area Melting (DAM). This process utilises customised architectural arrays of low power laser diode emitters for high speed parallel processing of metallic feedstock. Individually addressable diode emitters are used to selectively melt feedstock from a pre-laid powder bed. The laser diodes operate at shorter laser wavelengths (808 nm) than conventional SLM fibre lasers (1064 nm) theoretically enabling more efficient energy absorption for specific materials. The melting capabilities of the DAM process were tested for low melting point eutectic BiZn2.7 elemental powders and higher temperature pre-alloyed 17-4 stainless steel powder. The process was shown to be capable of fabricating controllable geometric features with evidence of complete melting and fusion between multiple powder layers. Graphical abstract: Highlights: A novel highly scalable multi-laser powder bed additive manufacturing approach for processing metallic alloys. Near full melting of stainless steel alloy powder (99.7% density) using customised low power diode emitters (2.63 W). Increased laser absorption and reduced laser power requirement through use of shorter laser wavelength.